(-)-6 alpha-Hydroxy polyanthellin A - a novel antifouling diterpenoid from the Indian soft coral Cladiella krempfi (Hickson) - Mol, V. P. Limna; Raveendran, T. V.; Parameswaran, P. S.; Kunnath, R. J.; Rajamohanan, P. R. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2011)
Bioassay-guided purification of methanol extract of the soft coral Cladiella krempfi (Octocorallia: Alcynocea) yielded a novel eunicellin-type diterpenoid, (-)-6 alpha-hydroxy polyanthellin A (1), active against the cyprids of the fouling barnacle, Balanus amphitrite (EC(50) 9.02 mu g/mL; LC(50) 36 mu g/mL; and therapeutic ratio = 4). The structure of compound 1 was determined from its spectral data, including IR, NMR (1D and 2D NMR), and mass spectra.
Keywords: antifouling; Balanus amphitrite; biofouling; Cladiella krempfi; diterpenes